2023
DOI: 10.1002/jsfa.13081
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the versatility of carbohydrates in surimi and surimi products: novel applications and future perspectives

Zhang Sijin,
Liangzi Zhang,
Tao Yin
et al.

Abstract: Carbohydrate is one kind of the most important additives in the production of surimi and surimi products, mainly due to its wide range of sources and superior functionality. In recent years, new carbohydrate (oligosaccharides and polysaccharides) has been gradually applied in the production of surimi and surimi products which is mainly driven by consumer's requirement on nutritional and the flavors or taste quality and producer's requirement on extending the shelf life, like low calorie intake, dietary fiber e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Inulin has also been recognized as an additive for the frozen storage of surimi products. It can better maintain the surimi gel properties and alleviate the water loss during thawing …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inulin has also been recognized as an additive for the frozen storage of surimi products. It can better maintain the surimi gel properties and alleviate the water loss during thawing …”
Section: Introductionmentioning
confidence: 99%
“…It can better maintain the surimi gel properties and alleviate the water loss during thawing. 33 In this study, we first reported the feasibility and put forward the mechanism of inulin as a novel CPA for RBC cryopreservation. With the addition of inulin, thawed RBC recovery could be significantly improved and RBC properties were well maintained.…”
Section: Introductionmentioning
confidence: 99%